100% found this document useful (1 vote)
136 views

Lecture 2: Proof Techniques: BBM 205 Discrete Mathematics Hacettepe University

This document provides an overview of proof techniques taught in the BBM 205 Discrete Mathematics course at Hacettepe University. It discusses direct proofs, proof by contrapositive, proof by contradiction, and proof by cases. Examples are given for each type of proof. The learning objectives are also stated as direct proofs, proof by contrapositive, proof by contradiction, and proof by cases.

Uploaded by

ABUBAKAR ALI
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
100% found this document useful (1 vote)
136 views

Lecture 2: Proof Techniques: BBM 205 Discrete Mathematics Hacettepe University

This document provides an overview of proof techniques taught in the BBM 205 Discrete Mathematics course at Hacettepe University. It discusses direct proofs, proof by contrapositive, proof by contradiction, and proof by cases. Examples are given for each type of proof. The learning objectives are also stated as direct proofs, proof by contrapositive, proof by contradiction, and proof by cases.

Uploaded by

ABUBAKAR ALI
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 35

BBM 205 Discrete Mathematics

Hacettepe University
http://web.cs.hacettepe.edu.tr/∼bbm205

Lecture 2: Proof Techniques


Lecturer: Lale Özkahya

Resources:
Kenneth Rosen, Discrete Mathematics and App.
cs.colostate.edu/ cs122/.Spring15/home_resources.php
http://www.cs.nthu.edu.tw/ wkhon/math16.html
Proof Terminology

Theorem: statement that can be shown to be true


Proof: a valid argument that establishes the truth of a
theorem
Axioms: statements we assume to be true
Lemma: a less important theorem that is helpful in the
proof of other results
Corollary: theorem that can be established directly from
a theorem that has been proved
Conjecture: statement that is being proposed to be a
true statement
Learning objectives
• Direct proofs
• Proof by contrapositive
• Proof by contradiction
• Proof by cases
Technique #1: Direct Proof

• Direct Proof:
– First step is a premise
– Subsequent steps use rules of inference or
other premises
– Last step proves the conclusion
Methods of Proving
• A direct proof of a conditional statement
pq
first assumes that p is true, and uses axioms,
definitions, previously proved theorems, with
rules of inference, to show that q is also true
• The above targets to show that the case where
p is true and q is false never occurs
– Thus, p  q is always true
5
Direct Proof (Example 1)
• Show that
if n is an odd integer, then n2 is odd.
• Proof :
Assume that n is an odd integer. This implies
that there is some integer k such that
n = 2k + 1.
Then n2 = (2k+1)2 = 4k2 + 4k + 1 = 2(2k2 + 2k) + 1.
Thus, n2 is odd.
6
Direct Proof (Example 2)
• Show that
if m and n are both square numbers,
then m n is also a square number.
• Proof :
Assume that m and n are both squares. This
implies that there are integers u and v such that
m = u2 and n = v2.
Then m n = u2 v2 = (uv)2. Thus, m n is a square.
7
Class Exercise

• Prove: If n is an even integer, then n2 is even.

– If n is even, then n = 2k for some integer k.

– n2 = (2k)2 = 4k2

– Therefore, n = 2(2k2), which is even.


Can you do the formal version?

Step Reason
1. n is even Premise
2. kZ n = 2k Def of even integer in (1)
3. n2 = (2k)2 Squaring (2)
4. = 4k2 Algebra on (3)
5. = 2(2k2) Algebra on (4)
6.  n2 is even Def even int, from (5)
Technique #2:
Proof by Contrapositive
• A direct proof, but starting with the contrapositive
equivalence:
• p  q  q  p
• If you are asked to prove p  q
• you instead prove q  p
• Why? Sometimes, it may be easier to directly prove
q  p than p  q
Methods of Proving
• The proof by contraposition method makes use
of the equivalence
pq  qp

• To show that the conditional statement p  q


is true, we first assume  q is true, and use
axioms, definitions, proved theorems, with
rules of inference, to show  p is also true

8
Proof by Contraposition (Example 1)
• Show that
if 3n + 2 is an odd integer, then n is odd.
• Proof :
Assume that n is even. This implies that
n = 2k for some integer k.
Then, 3n + 2 = 3(2k) + 2 = 6k + 2 = 2(3k + 1),
so that 3n + 2 is even. Since the negation of
conclusion implies the negation of hypothesis,
the original conditional statement is true
9
Proof by Contraposition (Example 2)
• Show that
if n = a b, where a and b are positive,
then a   n or b   n .
• Proof :
Assume that both a and b are larger than  n .
Thus, a b  n so that n  a b. Since the
negation of conclusion implies the negation of
hypothesis, the original conditional statement
is true
10
Proof by contrapositive
Prove: If n2 is an even integer, then n is even.
(n2 even) → (n even)
By the contrapositive: This is the same as showing that
•¬(n even) → ¬(n2 even)
•If n is odd, then n2 is odd.
•We already proved this on slides 4 and 5.
Since we have proved the contrapositive:
¬(n even) → ¬(n2 even)
We have also proved the original hypothesis:
(n2 even) → (n even)
Technique #3:
Proof by contradiction
Prove: If p then q.
Proof strategy:
• Assume the negation of q.
• In other words, assume that p q is true.
• Then arrive at a contradiction p p (or something
that contradicts a known fact).
• Since this cannot happen, our assumption must be
wrong.
• Thus, q is false. q is true.
Proof by contradiction example
Prove: If (3n+2) is odd, then n is odd.
Proof:
•Given: (3n+2) is odd.
•Assume that n is not odd, that is n is even.
•If n is even, there is some integer k such that n=2k.
•(3n+2) = (3(2k)+2)=6k+2 = 2(3k+1), which is 2 times a number.
•Thus 3n+2 turned out to be even, but we know it’s odd.
•This is a contradiction. Our assumption was wrong.
•Thus, n must be odd.
Proof by Contradiction Example
Prove that the 2 is irrational.
Assume that “ 2 is irrational” is false, that is, 2 is rational.
a
Hence, 2 = and a and b have no common factors. The fraction
b
is in its lowest terms.
So a2 = 2b, 2 which means a must be even,
Hence, a = 2c
Therefore, b = 2c then b must be even, which means a and b
2 2

must have common factors.


Contradiction.
Technique #4:
Proof by cases
• Given a problem of the form:
• (p1  p2  …  pn)  q
• where p1, p2, … pn are the cases
pq

• This is equivalent to the following:


• [(p1  q)  (p2  q)  …  (pn  q)]
• So prove all the clauses are true.
Proof by cases (example)
• Prove: If n is an integer, then n2 ≥ n
• (n = 0  n ≥ 1  n ≤ -1)  n2 ≥ n
• Show for all the three cases, i.e.,
pq
• (n = 0  n2 ≥ n)  (n ≥ 1  n2 ≥ n)
 (n ≤ -1 n2 ≥ n)
• Case 1: Show that n = 0  n2 ≥ n
• When n=0, n2= 0.
• 0=0 
Proof by cases (example contd)
• Case 2: Show that n ≥ 1  n2 ≥ n
• Multiply both sides of the inequality n ≥ 1
by n
• We get n2 ≥ n p  q
Proof by cases (example contd)
• Case 3: Show that n ≤ -1 n2 ≥ n
• Given n ≤ -1,
• We know that n2 cannot be negative, i.e., n2 >
0
pq
• We know that 0 > -1
• Thus, n2 > -1. We also know that -1 ≥ n (given)
• Therefore, n2 ≥ n
Proof by Cases Example

Theorem: Given two real numbers x and y,


abs(x*y)=abs(x)*abs(y)

Exhaustively determine the premises


Case p1: x>=0, y>=0, so x*y>=0 so abs(x*y)=x*y and
abs(x)=x and abs(y)=y so abs(x)*abs(y)=x*y
Case p2: x<0, y>=0
Case p3: x>=0, y<0
Case p4: x<0, y<0
Methods of Proving
• When proving bi-conditional statement, we
may make use of the equivalence
pq  (pq)(qp)

• In general, when proving several propositions


are equivalent, we can use the equivalence
p1  p2  …  pk
 ( p1  p2 )  ( p2  p3 )  …  ( pk  p1 )

18
Proofs of Equivalence (Example)
• Show that the following statements about the
integer n are equivalent :
p := “n is even”
q := “n – 1 is odd”
r := “n2 is even”

• To do so, we can show the three propositions


p  q, q  r, r  p
are all true. Can you do so ?
19
Methods of Proving
• A proof of the proposition of the form x P(x )
is called an existence proof
• Sometimes, we can find an element s, called a
witness, such that P(s) is true
This type of existence proof is constructive
• Sometimes, we may have non-constructive
existence proof, where we do not find the
witness

20
Existence Proof (Examples)
• Show that there is a positive integer that can be
written as the sum of cubes of positive integers
in two different ways.
• Proof: 1729 = 13 + 123 = 93 + 103

• Show that there are irrational numbers r and s


such that rs is rational.
• Hint: Consider ( 2  2 ) 2

21
Common Mistakes in Proofs
• Show that 1 = 2.
• Proof : Let a be a positive integer, and b = a.
Step Reason
1. a = b Given
2. a2 = a b Multiply by a in (1)
3. a2 – b2 = a b – b2 Subtract by b2 in (2)
4. (a – b)(a + b) = b(a – b) Factor in (3)
5. a + b = b Divide by (a – b) in (4)
6. 2b = b By (1) and (5)
7. 2 = 1 Divide by b in (6)
22
Common Mistakes in Proofs
• Show that
if n2 is an even integer, then n is even.
• Proof :
Suppose that n2 is even.
Then n2 = 2k for some integer k.
Let n = 2m for some integer m.
Thus, n is even.

23
Common Mistakes in Proofs
• Show that
if x is real number, then x2 is positive.
• Proof : There are two cases.
Case 1: x is positive
Case 2: x is negative
In Case 1, x2 is positive.
In Case 2, x2 is also positive
Thus, we obtain the same conclusion in all
cases, so that the original statement is true.
24
Proof Strategies
• Adapting Existing Proof
• Show that
 3 is irrational.

• Instead of searching for a proof from nowhere,


we may recall some similar theorem, and see
if we can slightly modify (adapt) its proof to
obtain what we want
25
Proof Strategies
• Sometimes, it may be difficult to prove a
statement q directly

• Instead, we may find a statement p with the


property that p  q, and then prove p
Note: If this can be done, by Modus Ponens, q is true

• This strategy is called backward reasoning

26
Backward Reasoning (Example)
• Show that for distinct positive real numbers x and y,
0.5 ( x + y )  ( x y )0.5
• Proof: By backward reasoning strategy, we find that
1. 0.25 ( x + y )2  x y  0.5 ( x + y )  ( x y )0.5
2. ( x + y )2  4 x y  0.25 ( x + y )2  x y
3. x 2 + 2 x y + y2  4 x y  ( x + y ) 2  4 x y
4. x 2 – 2 x y + y2  0  x2 + 2 x y + y 2  4 x y
5. ( x – y )2  0  x2 – 2 x y + y2  0
6. ( x – y )2  0 is true, since x and y are distinct.
Thus, the original statement is true.
27
Interesting Examples

Can a checkerboard be tiled by 1  2 dominoes?

28
Interesting Examples

What if the top left corner is removed ?

29
Interesting Examples

What if the lower right corner is also removed ?

30

You might also like